Small-sample BOD₅ interval prediction for aeration recommendation using conformal calibrated LightTransformer-LGBM model - Wangben Zhao; Yuling Liu; Lu Wang; Shuaishuai Li; Li Sun; Shuang Ren (Journal of Environmental Chemical Engineering, 2026)

Incorporating dynamic ozone stress and parameter optimization into the BEPS model for improved GPP simulation - Jian Wang; Yuling Du; Jibo Yue; Tianxiang Cui; Yumin Chen; Lin Sun; Lei Shi (Ecological Modelling, 2026)

Using transgenic zebrafish to assess the effects of SCCPs exposure on embryonic neural development and its potential mechanisms - Jinxian Yang; Ruiyao Huang; Jin Wang; Mengna Jiang; Fengxu Wang; Yuling Jiang; Jiaxin Liu; Mingjing Sun; Sheng Chen; Tian Zhou; Xinyuan Zhao; Shunxing Zhu (Chemico-Biological Interactions, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Improving embryo rescue efficiency in seedless grape breeding with zeatin - Xi Chen; Shaopeng Zhao; Xinyu Chen; Mengyu Ma; Xue Wen; Yao Xiao; Yong Wang; Yuling Li; Feng Sun; Guotian Liu; Tingting Chen; Yan Xu (Protoplasma, 2026)

Antioxidant activities of three enzymatic hydrolysates from Stichopus japonicus on HaCaT cells in vitro and zebrafish in vivo - Xue Li; Fanying Meng; Tong Sun; Renfang Zhang; He Sun; Xinting Shao; You-Jin Jeon; Yong Li; Yuling Ding (Natural Product Research, 2026)

Development and Validation of An HPLC Method for Isolation and Structural Elucidation of Impurities in Chlorogenic Acid Self-Microemulsion Formulations - Yue Gao; Yanan Wang; Jing Xu; Ming Ji; Dongyang Zhao; Yanqi Han; Longhui Hao; Yi Zhang; Ying Sun; Zhenshuai Qin; Jun Ye; Hongliang Wang; et al. (Journal of Pharmaceutical Innovation, 2026)

Evidence for Early Middle Jurassic wildfires: New macro-charcoal records from the Xishanyao Formation, Junggar Basin, Northern Xinjiang, China - Bing Yang; Yuling Na; Xiao Shi; Yi Wei; Xinzhi Zhang; Bing Wang; Siyuan Sun; Weitong Li (Review of Palaeobotany and Palynology, 2026)

An improved Hydrology-Informed attention LSTM(HIA-LSTM) model for runoff simulation with seasonal snowmelt - Muwu Ling; Yashuo Guan; Yanqing Lian; Xiaonan Sun; Yongliang Gao; Yuling Ren (Journal of Hydrology, 2026)

A novel vacuum steam – Microwave thawing of frozen pork - Fangran Liu; Weidong Wu; Hua Zhang; Yuyao Sun; Yuling Liu (Journal of Food Engineering, 2026)

Efficient biosynthesis of vitamin B6 based on DXP-independent pathway in Bacillus subtilis - Lingqing Zeng; Jiawei Sun; Yuling Chen; Yongzhong Wang; Yingwu Yang (Food Bioscience, 2026)

Responses of viral communities and viral-encoded auxiliary metabolic genes to long-term fertilization practices under different land-use types - Xunqi Chen; Dong Zhu; Yuling Zheng; Xiaomin Li; Guoxin Sun; Xiaoming Li; Longjun Ding (Journal of Environmental Sciences, 2026)

Tryptophan metabolism alterations in neurological and psychiatric diseases: Molecular mechanisms and pharmacological targets - Yuanyuan Wang; Yuling Chen; Hongtao Li; Jingjing Sang; Chen Chen; Lei Xu; Weiting Zhang; Baichen Xiong; Ruijia Jiang; Xinyu Ren; Yao Chen; Haopeng Sun; et al. (Metabolic Brain Disease, 2026)

A decision support system for coagulant dosage using explainable NSGA-II optimized stacking framework - Wangben Zhao; Yuling Liu; Lu Wang; Shuaishuai Li; Li Sun; Ren Shuang (Journal of Water Process Engineering, 2026)

Corrigendum to “Soil iGDGTs temperature dependence: From the Tibetan Plateau to the global scale and its implications for the Holocene temperature conundrum” [Geochim. Cosmochim. Acta 411 (2025) 233–249] - Yanwu Duan; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Yuling Zhou; Yuanxin Li; Mengjing Li; Lin Chen; Xianyong Cao; Fahu Chen (Geochimica et Cosmochimica Acta, 2026)

Multistimuli-responsive degradable metal-organic framework nanoplatform potentiates photoimmunotherapy for hepatocellular carcinoma via cGAS-STING pathway activation - Yahui Wu; Zhipu Liu; Yi Zhang; Senfeng Zhao; Miaoqing Li; Ruiyang Zhang; Jiahui Cao; Peng Liu; Liming Song; Yin Liu; Yunpeng Zhai; Weijie Wang; et al. (Chemical Engineering Journal, 2026)

Deciphering the mechanism of aristolochic acid I-driven hepatocellular carcinoma through integrated network toxicology and bioinformatics - Yuling Liang; Xing Ning; Qiuxia Chen; Shuqiao Zhang; Huishan Luo; He Yu; Tangjiaqi Li; Baoguo Sun; Shijun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Development and simulation-based optimization of a Split-flow low-aerobic/anoxic/Oxic process integrating partial nitrification -denitrification with step feeding for enhanced nitrogen removal - Li Sun; Yuling Liu; Hao Shu; Yaohui Shao; Zhiqiang Xu; Jiayu Qi (Journal of Water Process Engineering, 2026)

Improving PCR-GLOBWB 2 to model regional water stress dynamics under climate and socioeconomic change scenarios - Yashuo Guan; Yanqing Lian; Muwu Ling; Yongliang Gao; Yuling Ren; Xiaonan Sun (Journal of Hydrology, 2026)

Identifying impact factors of long-term ecological vulnerability using multivariate wavelet coherence analysis - Yuling Ren; Yanqing Lian; Muwu Ling; Saurabh Mishra; Yongliang Gao; Yashuo Guan; Xiaonan Sun (Journal of Hydrology, 2026)

Antimicrobial mechanism of moderate-temperature-assisted high-voltage pulsed electric field combined with vanillin against Saccharomyces cerevisiae and its application in red raspberry juice - Yuling He; Bin Li; Xiyun Sun; Xu Xie; Junwei Huo; Fuzhi Xuan; BaoRu Yang; Ying Zhou; Yuehua Wang (Innovative Food Science & Emerging Technologies, 2025)

Soil iGDGTs temperature dependence: From the Tibetan Plateau to the global scale and its implications for the Holocene temperature conundrum - Yanwu Duan; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Yuling Zhou; Yuanxin Li; Mengjing Li; Lin Chen; Xianyong Cao; Fahu Chen (Geochimica et Cosmochimica Acta, 2025)

Machine learning-assisted identification of core flavor compounds and prediction of core microorganisms in fermentation grains and pit mud during the fermentation process of strong-flavor Baijiu - Jiang Xie; Jiaxin Hong; Chunsheng Zhang; Xin Yuan; Zhigang Zhao; Dongrui Zhao; Shimin Wang; Baoguo Sun; Ran Ao; Jinyuan Sun; Yuling Sun; Mingquan Huang; et al. (Food Chemistry, 2025)

Recombinant PD1 liposome loading nintedanib for pulmonary fibrosis therapy in mice - Qian Luo; Ying Xie; Jiarui Xu; Yuxin Ren; Shuyuan Xiong; Hongrui Zhang; Yuling Chen; Haocheng Chen; Jinling Wang; Pengyu Huang; Liyu Sun; Peishan Li; et al. (Chemical Engineering Journal, 2025)

Divergent environmental controls on branched tetraethers along precipitation gradients in soils of the Tibetan Plateau - Yanwu Duan; Yuling Zhou; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Lin Chen; Yuanxin Li; Mengjing Li; Xianyong Cao; Fahu Chen (Chemical Geology, 2025)

High-throughput discrimination of chlorogenic acid isomers in Lonicerae Japonicae Flos by U-shaped mobility analyzer-mass spectrometer - Meng Ding; Luwei Zheng; Ao Zhou; Yuling Li; Yiming Wang; Xiaoqiang Zhang; Wenjian Sun; Wen Gao; Ping Li; Hua Yang (Food Chemistry, 2025)

Fluorine-decorated rare-earth hydroxides mediated preparation of hollow low-iridium oxyfluoride for highly efficient oxygen evolution reaction catalyst - Yuling Hu; Zhen Zeng; Yun Liu; Hao Zhang; Wenjuan Shi; Zhengye Kang; Yuliang Yuan; Wei Sun; Xinlong Tian (Chemical Engineering Journal, 2025)

KHDC3 affects the lineage differentiation of early embryo by regulating the differential distribution of YAP signal - Qian Xu; Yuling Lin; Lina Yu; Yang Zhang; Na Kong; Guijun Yan; Haixiang Sun; Guangyi Cao (Theriogenology, 2025)

Fractional-order constitutive model of loess creep incorporating microstructural damage under seepage-stress coupling effect - Zhou Chang; Changgen Yan; Hengxing Lan; Shengwen Qi; Han Bao; Yuling Shi; Weifeng Sun (Engineering Geology, 2025)

Untargeted lipidomic deep-profiling of human plasma via high-performance aza-Prilezhaev aziridination-LC-MS: Unraveling C C isomeric signatures of Charcot-Marie-Tooth disease - Yuling Li; Weiran Zhao; Xiang Xiang; Yunlei Hu; Xiaoqiang Zhang; Wenjian Sun; Xiaoxuan Liu (Analytica Chimica Acta, 2025)

Plant-insect interaction from the Middle Jurassic Haifanggou Formaton in Huludao, western Liaoning and its geological implications - Yuling Na; Tao Li; Yunfeng Li; Chunlin Sun; Xiao Shi; Xuemei Li (Palaeobiodiversity and Palaeoenvironments, 2025)

Water stress exacerbated by altered flow pathways in the Tibetan plateau: A critical analysis - Yuling Ren; Saurabh Mishra; Yanqing Lian; Jianyun Zhang; Junliang Jin; Ke Zhang; Weiguang Wang; Yongliang Gao; Yashuo Guan; Muwu Ling; Xiaonan Sun (Environmental Impact Assessment Review, 2025)

Black soldier fly larvae (Diptera: Stratiomyidae) enhance stabilization and modulate substrate microbial communities during municipal sewage sludge biotransformation - Weiping Tian; Zhouqiang Wang; Yu Xing; Yandong Xie; Yuling Jian; Haizhao Sun (Journal of Environmental Chemical Engineering, 2025)

AIE-based dual-ratiometric chemosensor for detection of sulfur dioxide derivatives and viscosity and its application in food samples and biological imaging - Na Tang; Ruian Sun; Kangshuo Xu; Haichang Ding; Yuling Zeng; Yuan Ji; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2025)

Correction to: Failure mechanism and stability evaluation of rockslides with oblique intersecting faults as well as mitigation measures for slope − top platform collapse - Huaixin Li; Changgen Yan; Yuling Shi; Hengxing Lan; Han Bao; Weifeng Sun; Zhe He; Dingle Ma; Kui Wen; Jiamin Hu (Landslides, 2025)

Isotopic and hydrochemical evidence for the origins of unconventional gases in the Middle and Lower Jurassic coal measures in the Fukang area of Junggar Basin, NW China - Jie Xiang; Jiandong Li; Xianqing Li; Xiaomin Ma; Jie Sun; Zhuo Zou; Yuling Qin (International Journal of Coal Geology, 2025)

Peptides from Dalian Stichopus japonicus: Antioxidant Activity and Melanogenesis Inhibition In Vitro Cell Models and In Vivo Zebrafish Models Guided by Molecular Docking Screening - Xue Li; Fanying Meng; Tong Sun; Zezhuang Hao; Yihua Wang; Yunfei Jiang; Ye Wang; Yong Li; Yuling Ding (Marine Biotechnology, 2025)

Failure mechanism and stability evaluation of rockslides with oblique intersecting faults as well as mitigation measures for slope − top platform collapse - Huaixin Li; Changgen Yan; Yuling Shi; Hengxing Lan; Han Bao; Weifeng Sun; Zhe He; Dingle Ma; Kui Wen; Jiamin Hu (Landslides, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

Constructing a low-cost total Ce(III)-based adsorbent for efficient removal and recovery of phosphate - Tao Zhang; Junle Li; Dongqing Liu; Yuling Ma; Yu Han; Sujie Shan; Kai Sun; Elena V. Zelinskaya; Aijie Wang; Hongliang Sun; Wei Wang (Chemical Engineering Journal, 2025)

Effective enhancement of ramie anaerobic continuous flow degumming by chitosan and its microbiological mechanism - Xuehui Xie; Yiting Qin; Haonan Mo; Zhuoyu Zhao; Yuling Li; Yanxue Ma; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; Qingyun Zhang; Xiaoguang Chen (Bioresource Technology, 2025)

Eliminating the effect of pH: Dual-matrix modulation adsorbent enables efficient lithium extraction from concentrated seawater - Yu Han; Liuqian An; Yan Yang; Yuling Ma; Hongliang Sun; Jinxin Yao; Tao Zhang; Wei Wang (Water Research, 2025)

Determining optimal nitrogen concentration intervals throughout lettuce growth using fluorescence parameters - Peizhe Li; Zhangtong Sun; Yongxia Yang; Miao Lu; Huimin Li; Haoran Yan; Jin Hu; Yuling Song (Computers and Electronics in Agriculture, 2024)

A multi-perspective assessment of satellite surface Ozone products in China: Spatiotemporal variability, land cover impacts and pollution monitoring capability - Jian Wang; Yuling Du; Tianxiang Cui; Jibo Yue; Lin Sun; Haiping Si; Ping Dong; Hebing Liu; Yong Li; Lei Shi (Remote Sensing Applications: Society and Environment, 2024)

Ecological impacts of vermiculite and submerged macrophytes on sediment enzyme activity in lake restoration: Insights from the mesocosm study - Chenxu Zhao; Yuling Liu; Zixuan Yan; Wangben Zhao; Jiayu Sun (Journal of Water Process Engineering, 2024)

Comparative analysis of anaerobic degumming effects on different bast fibers from the angle of enzyme activity and microbial community structure - Yiting Qin; Xuehui Xie; Haonan Mo; Yuling Li; Xiaoguang Chen; Yanxue Ma; Zhuoyu Zhao; Hangmi Zheng; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; et al. (Journal of Cleaner Production, 2024)

Microplastics–biofilm in aquatic ecosystem: Formation, pollutants complexation, greenhouse gas emission and ecotoxicology - Saurabh Mishra; Yuling Ren; Xiaonan Sun; Yanqing Lian; Anurag Kumar Singh; Niraj Sharma; K.C. Shikhar (Journal of Environmental Management, 2024)

Enhanced generation and effective utilization of H2O2 for simultaneous aging of plastics in the C3N4/Vis-LED system with the addition of phenol - Xiaoman Zhang; Ting Zhang; Hongyang Guo; Shuqi Wan; Xiaodan Liu; Jianhui Sun; Yuling Zhao; Shuying Dong; Xianfa Su; Maohong Fan (Chemical Engineering Journal, 2024)

A turn-off xanthene-based fluorescent probe for detection of cysteine and its practical application in bioimaging and food samples - Na Tang; Kangshuo Xu; Ruian Sun; Haichang Ding; Yuling Zeng; Yuan Ji; Congbin Fan; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2024)

First wetland mapping at 10-m spatial resolution in South America using multi-source and multi-feature remote sensing data - Weiwei Sun; Gang Yang; Yuling Huang; Dehua Mao; Ke Huang; Lin Zhu; Xiangchao Meng; Tian Feng; Chao Chen; Yong Ge (Science China Earth Sciences, 2024)

A review of the research progress on Artemisia argyi Folium: botany, phytochemistry, pharmacological activities, and clinical application - Hailong Wang; Yiwen Zhang; Denghui Yu; Yong Li; Yuling Ding; Yuan He; Li Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Combining effects of submerged macrophytes and lanthanum-modified bentonite on sediment enzyme activity: Evidence from mesocosm study - Chenxu Zhao; Yuling Liu; Zixuan Yan; Wangben Zhao; Jiayu Sun (Chemosphere, 2024)

Microplastics pollution in the Asian water tower: Source, environmental distribution and proposed mitigation strategy - Saurabh Mishra; Yuling Ren; Xiaonan Sun; Yanqing Lian; Anurag Kumar Singh; Niraj Sharma (Environmental Pollution, 2024)

A pH transformable nanocarrier for gradual and precise delivery of a natural immunomodulator and chemotherapy agent to trigger tumor apoptosis - Qianwen Sun; Wei Chen; Qi Zhang; Yanqi Han; Yue Gao; Jun Ye; Hongliang Wang; Yi Zhang; Lili Gao; Yuling Liu; Yanfang Yang (Chemical Engineering Journal, 2024)

Study on the chemical composition and anti-fungi activities of anthraquinones and its glycosides from Rumex japonicus Houtt. - He Sun; Dandan Xiao; Xue Li; Tong Sun; Fanying Meng; Xinting Shao; Yuling Ding; Yong Li (Journal of Natural Medicines, 2024)

N6-methyladenosine (m6A) Writer WTAP Potentiates Hepatocellular Carcinoma Immune Evasion and Aerobic Glycolysis - Fatao Yu; Yuling Feng; Qing Wang; Jian Sun (Cell Biochemistry and Biophysics, 2024)

Distribution, mobilization, risk assessment and source identification of heavy metals and nutrients in surface sediments of three urban-rural rivers after long-term water pollution treatment - Xu Yao; Zheng Wang; Dandan Li; Hejia Sun; Chong Ren; Yilei Yu; Feifei Pei; Yuling Li (Science of The Total Environment, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

The hysteresis damage of cold exposure on tissue and transcript levels in mice - Jing Zhang; Shiwan You; Lan Yu; Yuling Zhang; Zuoping Li; Na Zhao; Bo Zhang; Lihua Kang; Shiguo Sun (Journal of Thermal Biology, 2024)

Eocene lacustrine microbialites in the western Qaidam Basin, China: implication for the sedimentary record and hydrocarbon potential - Xiang Li; Jiangong Wang; Guohui Long; Li Xu; Jun Cui; Xiujian Sun; Yuling Wang (Carbonates and Evaporites, 2024)

Lysosome-targeted ruthenium(II) complex encapsulated with pluronic® F-127 induces oncosis in A549 cells - Nanlian Pan; Yuqing Zhang; Minying Huang; Zhijun Liang; Yao Gong; Xide Chen; Yuling Li; Ciling Wu; Zunnan Huang; Jing Sun (JBIC Journal of Biological Inorganic Chemistry, 2024)

Exploring low-carbon mulching strategies for maize and wheat on-farm: Spatial responses, factors and mitigation potential - Huihui Wei; Kaiping Zhang; Ning Chai; Yue Wang; Yuling Li; Jianjun Yang; Matthew Tom Harrison; Ke Liu; Pingxing Wan; Wenjuan Zhang; Guojun Sun; Zhansheng Li; et al. (Science of The Total Environment, 2024)

Well-known polypeptides of deer antler velvet with key actives: modern pharmacological advances - He Sun; Dandan Xiao; Wei Liu; Xue Li; Zhe Lin; Yong Li; Yuling Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Dysregulated PD-L2 is correlated with disease activity and inflammation in rheumatoid arthritis - Jian Xiong; Jie Yang; Yuling Sun; Yachun Chen; Yundi Guo; Cuiping Liu; Jing Sun (Immunogenetics, 2023)

V-ATPase V0 subunit activation mediates maduramicin-induced methuosis through blocking endolysosomal trafficking in vitro and in vivo - Yuling Zheng; Jing Xiao; Junqi Wang; Bin Dong; Dawei Guo; Hui Ji; Haifeng Sun; Lin Peng; Shanxiang Jiang; Xiuge Gao (Food and Chemical Toxicology, 2023)

A novel oral biomimetic delivery system enhancing both the mucosal and systemic immunity of influenza virus vaccine - Hongyan Lu; Yikun Gao; Jianmin Chen; Jing Chai; Ansheng Li; Tongtong Sun; Yuling Mao; Ye He; Qinfu Zhao; Jinghai Zhang; Siling Wang (Chemical Engineering Journal, 2023)

The miR156x + p/SPL13-6 module responds to ABA, IAA, and ethylene, and SPL13-6 participates in the juvenile–adult phase transition in Pyrus - Minyan Song; Anqi Li; Lei Sun; Yuling Mei; Zhiyan Wang; Rihong Wang; Ran Wang; Dingli Li; Jiankun Song; Chunxiang Zhang; Yingjie Yang (Horticulture, Environment, and Biotechnology, 2023)

The cotton pectin methyl esterase gene GhPME21 functions in microspore development and fertility in Gossypium hirsutum L. - Yihan Xu; Yanhua Jiang; Junye Jiao; Hongli Zheng; Yuqing Wu; Yuling Li; Rayhangul Abdursul; Yanyan Zhao; Liping Ke; Yuqiang Sun (Plant Molecular Biology, 2023)

The increased medical burden associated with frailty is partly attributable to household solid fuel: A nationwide prospective study of middle-aged and older people in China - Xiaoyu Jin; Yuling Wang; Yudong Wu; Yunfeng Liang; Yuxuan Li; Xiaoni Sun; Shuangshuang Yan; Lu Mei; Junwen Tao; Jian Song; Rubing Pan; Weizhuo Yi; et al. (Science of The Total Environment, 2023)

Mechanism of thermally activated sodium persulfate–biochar skeleton treatment to improve the dewaterability of waste activated sludge - Shuaishuai Li; Yuling Liu; Chuanchuan Dou; Ruihao Sun (Journal of Environmental Chemical Engineering, 2023)

Atmospheric particulate matter impairs cognition by modulating synaptic function via the nose-to-brain route - Chunmei Liang; Yuling Jiang; Tianzhen Zhang; Yao Ji; Yu Zhang; Yuanhong Sun; Shengnan Li; Yi Qi; Yan Wang; Yujie Cai; Tianwen Lai; Lili Cui (Science of The Total Environment, 2023)

Efficient determination of enantiomeric ratios of α-hydroxy/amino acids from fermented milks via ion mobility−mass spectrometry - Yuling Li; Li Zhang; Wenjian Sun; Kuofeng Tseng; Jing Zhang; Yinlong Guo (Food Chemistry, 2023)

Achieving highly efficient near-ultraviolet emitters via optimizing molecular configuration by the intramolecular-locked donor and acceptor - Daokun Zhong; Xiaolong Yang; Xuming Deng; Xi Chen; Yuling Sun; Peng Tao; Zikang Li; Jie Zhang; Guijiang Zhou; Wai-Yeung Wong (Chemical Engineering Journal, 2023)

Persistence of Digestive Enzyme Activities of Sea Cucumber (Apostichopus japonicus): Evidence From Diet Switch After Evisceration - Xueqi Li; Qinfeng Gao; Yuan Tian; Yaoping Mei; Yuling Xu; Yiming Cao; Shuanglin Dong; Yangen Zhou; Yongjun Sun; Wenming Ju (Frontiers in Marine Science, 2022)
A two-stage diet-switch experiment was conducted to examine the hypothesis that the changes in digestive enzyme activities of sea cucumber ( Apostichopus japonicus ) induced by historic diets might persist in the regenerated intestines. In stage I, A. japonicus were treated with two different diets for 56 days, including diet A with 11% crude protein, 1% crude lipid, and 40% carbohydrate, and diet B with 18% crude protein, 2% crude lipid, and 35% carbohydrate. In stage II, each treatment was subjected to evisceration with 0.35M KCl or not (eviscerated and non-eviscerated groups), half of which were then switched to different diets from diet A to B or vice versa for 112 days. The persistence of digestive enzyme activities was evaluated by measuring the changes in digestive enzyme activities before and after evisceration. In stage I, diets B and A increased trypsin and amylase activities, respectively. In stage II, the higher trypsin activities were observed in eviscerated and non-eviscerated A. japonicus that had consumed diet B in stage I. The higher amylase activities were observed only in eviscerated A. japonicus that had consumed diet A in stage I. It indicated that the historic diets showed long-term effects on the digestion of A. japonicus , which led to the persistence of changes in both trypsin and amylase activities in intestines, especially in the regenerated intestines. In addition, the specific growth rates (SGRs) and metabolic rates (MRs) of A. japonicus were affected by the long-term effects of historic diets. Meanwhile, the relationships between enzymic activities, SGRs, and MRs were observed in A. japonicus , indicating that the historic diets could produce long-term effects on the growth and metabolism of A. japonicus through their long-term effects of historic diets on digestive enzyme activities. In conclusion, the present study showed that the changes in digestive enzyme activities induced by different diets in stage I could persist in the intestines and regenerated intestines, leading to long-term effects of historic diets on the growth and metabolism of A. japonicus .

The comparative impact among different intensive statins and combination therapies with niacin/ezetimibe on carotid intima-media thickness: a systematic review, traditional meta-analysis, and network meta-analysis of randomized controlled trials - Hongwei Li; Xiaolin Xu; Liming Lu; Runlu Sun; Qi Guo; Qian Chen; Junjie Wang; Zhijian He; Yuling Zhang (European Journal of Clinical Pharmacology, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Economic policy choice of governing haze pollution: evidence from global 74 countries - Feng Dong; Xiaojie Zhang; Yajie Liu; Yuling Pan; Xiaoyun Zhang; Ruyin Long; Ziyuan Sun (Environmental Science and Pollution Research, 2021)

Molecular cloning and characterization of squalene synthase from Matricaria recutita L. - Xiaojuan Hou; Yuling Tai; Shuping Ling; Dahui Li; Chunxiao Guo; Jiameng Sun; Guifang Pan; Yi Yuan (Acta Physiologiae Plantarum, 2018)

Genetic dissection of wheat panicle traits using linkage analysis and a genome-wide association study - Kai Liu; Xiaoxiao Sun; Tangyuan Ning; Xixian Duan; Qiaoling Wang; Tongtong Liu; Yuling An; Xin Guan; Jichun Tian; Jiansheng Chen (Theoretical and Applied Genetics, 2018)

Genetic Dissection of Wheat Kernel Hardness Using Conditional QTL Mapping of Kernel Size and Protein-Related Traits - Xiaoxiao Sun; Tongtong Liu; Tangyuan Ning; Kai Liu; Xixian Duan; Xuerong Wang; Qiaoling Wang; Yuling An; Xin Guan; Ji-Chun Tian; Jian-Sheng Chen (Plant Molecular Biology Reporter, 2018)

Determination of seven pyrethroid pesticide residues in vegetables by gas chromatography using carboxylated multi-walled carbon nanotubes as dispersion solid phase extraction sorbent - Peng Sun; Yuling Gao; Chong Xu; Yongfu Lian (Food Additives & Contaminants: Part A, 2017)

Construction and characterization of a bacterial artificial chromosome library for Camellia sinensis - Yuling Tai; Hao Wang; Chaoling Wei; Ling Su; Min Li; Liqun Wang; Zhaozhao Dai; Lingyun Shao; Jiayue Jiang; Meizhong Luo; Hua Yang; Weiwei Deng; et al. (Tree Genetics & Genomes, 2017)

Silencing of six susceptibility genes results in potato late blight resistance - Kaile Sun; Anne-Marie A. Wolters; Jack H. Vossen; Maarten E. Rouwet; Annelies E. H. M. Loonen; Evert Jacobsen; Richard G. F. Visser; Yuling Bai (Transgenic Research, 2016)

Down-regulation of Arabidopsis DND1 orthologs in potato and tomato leads to broad-spectrum resistance to late blight and powdery mildew - Kaile Sun; Anne-Marie A. Wolters; Annelies E. H. M. Loonen; Robin P. Huibers; René van der Vlugt; Aska Goverse; Evert Jacobsen; Richard G. F. Visser; Yuling Bai (Transgenic Research, 2016)

Effects of epigallocatechin gallate on the cell-wall structure of Mycobacterial smegmatis mc 2 155 - Tieying Sun; Biaojie Qin; Mingchuan Gao; Yuling Yin; Changyuan Wang; Shizhu Zang; Xinli Li; Cuili Zhang; Yi Xin; Tao Jiang (Natural Product Research, 2015)

The Middle Jurassic palynology of the Daohugou area, Inner Mongolia, China, and its implications for palaeobiology and palaeogeography - Yuling Na; Steven R. Manchester; Chunlin Sun; Shuqin Zhang (Palynology, 2015)

Four novel antimicrobial peptides derived from human C8α-MACPF - Zhen Zhang; Yuling Zhou; Jing Sun; Peihong Mao; Xiang Jing; Xiangdong Ma; Lixin Ma (Biotechnology Letters, 2014)

Novel antimicrobial metabolites produced by Sika deer-associated Actinomyces sp. JN411010 - Yujiao Tang; Yanmei Wang; Zhaohui Wang; Jing Zhang; Jianchun Qin; Quankai Wang; Lihua Yang; Lingzhi Xu; Yuling Ding; Yang Guo; Hongliang Li; Jingsi Li; et al. (Natural Product Research, 2013)

Fine mapping of the Ph-3 gene conferring resistance to late blight (Phytophthora infestans) in tomato - Chunzhi Zhang; Lei Liu; Zheng Zheng; Yuyan Sun; Longxi Zhou; Yuhong Yang; Feng Cheng; Zhonghua Zhang; Xiaowu Wang; Sanwen Huang; Bingyan Xie; Yongchen Du; et al. (Theoretical and Applied Genetics, 2013)

Erratum to: Flavokawain B induces apotosis of non-small cell lung cancer H460 cells via Bax-initiated mitochondrial and JNK pathway - JunXia An; YaRong Gao; Jing Wang; QiYu Zhu; YuLing Ma; Jian Wu; Jian Sun; YaXiong Tang (Biotechnology Letters, 2012)

Flavokawain B induces apoptosis of non-small cell lung cancer H460 cells via Bax-initiated mitochondrial and JNK pathway - JunXia An; YaRong Gao; Jing Wang; QiYu Zhu; YuLing Ma; Jian Wu; Jian Sun; YaXiong Tang (Biotechnology Letters, 2012)

Production of diosgenin from yellow ginger (Dioscorea zingiberensis C. H. Wright) saponins by commercial cellulase - Wei Liu; Wen Huang; WeiLing Sun; YuLing Zhu; JinRen Ni (World Journal of Microbiology and Biotechnology, 2010)

Effects of vegetation control on ecosystem water use efficiency within and among four grassland ecosystems in China - ZHONGMIN HU; GUIRUI YU; YULING FU; XIAOMIN SUN; YINGNIAN LI; PEILI SHI; YANFEN WANG; ZEMEI ZHENG (Global Change Biology, 2008)
Through 2–3‐year (2003–2005) continuous eddy covariance measurements of carbon dioxide and water vapor fluxes, we examined the seasonal, inter‐annual, and inter‐ecosystem variations in the ecosystem‐level water use efficiency (WUE, defined as the ratio of gross primary production, GPP, to evapotranspiration, ET) at four Chinese grassland ecosystems in the Qinghai‐Tibet Plateau and North China. Representing the most prevalent grassland types in China, the four ecosystems are an alpine swamp meadow ecosystem, an alpine shrub‐meadow ecosystem, an alpine meadow‐steppe ecosystem, and a temperate steppe ecosystem, which illustrate a water availability gradient and thus provide us an opportunity to quantify environmental and biological controls on ecosystem WUE at different spatiotemporal scales. Seasonally, WUE tracked closely with GPP at the four ecosystems, being low at the beginning and the end of the growing seasons and high during the active periods of plant growth. Such consistent correspondence between WUE and GPP suggested that photosynthetic processes were the dominant regulator of the seasonal variations in WUE. Further investigation indicated that the regulations were mainly due to the effect of leaf area index (LAI) on carbon assimilation and on the ratio of transpiration to ET ( T /ET). Besides, except for the swamp meadow, LAI also controlled the year‐to‐year and site‐to‐site variations in WUE in the same way, resulting in the years or sites with high productivity being accompanied by high WUE. The general good correlation between LAI and ecosystem WUE indicates that it may be possible to predict grassland ecosystem WUE simply with LAI. Our results also imply that climate change‐induced shifts in vegetation structure, and consequently LAI may have a significant impact on the relationship between ecosystem carbon and water cycles in grasslands.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)